Compared Dexmedetomidine and Fentanyl on Sensory-Motor Block in Unilateral Intrathecal Anesthesia of Lower-limbs Orthopedic Surgeries: A Randomized Duble-blind Trials: - Shahroudi, Atefeh; Alipour , Mohammad; Purafzali Firouzabadi , Seyed Javad; Najaf Najafi , Mona; Molaei , Ehsan (Galen Medical Journal, 2022)
Background: One of the alternatives for lower-limb orthopedic surgery is spinal anesthesia. It can affect the hemodynamic status and cause the prolonged motor and sensory blocks, as well as urinary retention, which are less common in the unilateral technique. Different drugs are used to improve the quality of the block and reduce its complications. Dexmedetomidine, a selective alpha-2 adrenergic receptor agonist, and fentanyl, an opioid medication, could administration as an adjuvant to increase the intrathecal block quality. Hence, this study aimed to compare unilateral spinal anesthesia with bupivacaine/dexmedetomidine (BD) and bupivacaine/fentanyl (BF) regimes on the sensory-motor block among patients with lower-limb orthopedic surgeries. Materials and Method: This randomized, double-blind clinical trial was performed on 36 patients who underwent lower-limb orthopedic surgeries in Qaem Hospital, Mashhad, Iran. The patients were randomly divided into two groups. Patients who received 5.7 mg hyperbaric bupivacaine 0.5% plus 10 Âµg fentanyl (BF group) or 5 Âµg dexmedetomidine (BD group) were administered for inducing unilateral spinal anesthesia. Patients and investigators responsible for data collection were not awarded from allocation groups. The sensory-motor block level, duration, postoperative analgesia, and complications were recorded and compared between the two groups. Results: No significant difference was observed between the two groups in hemodynamic changes (i.e., systolic and diastolic blood pressure and heart rate) before and after the blockage (PËƒ0.05). Also, there was no difference in the sensory-motor block level and anesthesia-related complications between BF and BD groups (PËƒ0.05). Conclusion: In patients for whom the use of opioids for unilateral spinal anesthesia is contraindicated, dexmedetomidine could be considered an appropriate alternative.